Zur mathematischen Behandlung der Wasserdampfsorptionsisothermen quellbarer Stoffe - S. Gál; I. Tomka; R. Signer (CHIMIA)
The Sorption of water vapour by solids, built of chain shaped molecules, bearing atomic groupes, capable of forming hydrogen bonds with water, and being partially arranged in an irregulär, amorphous state, is treated theoretical. The theory is applied to the Sorption isotherm of Casein and is in fair agreement with the experiment.